A Self‐Assembled Rectangular Host with Terpyridine–Platinum(II) Moieties That Binds Unsubstituted Pentacene in Solution. Issue 9 (12th February 2016) - Yamaki, Yusuke; Nakamura, Takashi; Suzuki, Sayuri; Yamamura, Masaki; Minoura, Mao; Nabeshima, Tatsuya
Abstract: Pentacene has attracted much attention as an organic electric material, but it often suffers from its very low solubility. We now report self‐assembled rectangular host1 8+ that has two pairs of terpyridine–Pt II moieties aligned parallel to each other and connected by diyne linkers. The host encapsulated unsubstituted pentacene (2 ) with a remarkably strong binding constant of K a ≈ 10 7 M –1 and solubilized it in acetonitrile up to the millimolar level. For smaller acenes (i.e., naphthalene to tetracene), a planar arrangement of two molecules inside the cavity was achieved. These results made it possible to analyze the acenes in the solution phase and provided a way to align the guests by a solution‐processing method as a possible application, and thus, they contribute to fundamental physical organic chemistry as well as organic electronics. Abstract : A self‐assembled rectangular host with terpyridine–Pt II moieties encapsulates unsubstituted pentacene with a remarkably strong binding constant of K a ≈ 10 7 M –1 . Furthermore, a planar arrangement of two molecules of the smaller acenes (i.e., naphthalene to tetracene) is achieved inside the cavity.